Contribuicões ao estudo de consequências físicas de cordas cósmicas e do efeito Casimir em contexto cosmológico. - Mota, Herondy Francisco Santana (2013)
In the present thesis, we consider emission of Higgs particles by cosmic strings with condensates. Stringent constraints on cosmic string tension Gu are obtained by considering the effect of Higgs particles emission on photo-dissociation of lights elements and their contributions to the observed diffuse gamma-ray background (GRB) in the universe. The resulting constraints are obtained as a function of the coupling constant k to the cosmic string and are plotted on the (k;Gu)-plan. Then, we show that the production of Higgs particles by loops of cosmic strings is ruled out by observations of photo-dissociation and GRB unless Gu~ 10-19. Another effect we consider is the thermal Casimir effect. In this scenario, we calculate the total internal energy, total energy density and pressure, and the free energy for the neutrino and electromagnetic fields in Einstein and closed Friedmann cosmological models. The Casimir contributions to all these quantities are separated. The asymptotic expressions for both the total internal energy and free energy, and for the Casimir contributions to them are found in the limiting cases of low and high temperatures. It is shown that the neutrino field does not possess a classical limit at high temperature. As for the electromagnetic field, we demonstrate that the total internal energy has the classical contribution and the Casimir internal energy goes to the classical limit at high temperature. The respective Casimir free energy contains both linear and logarithmic terms with respect to the temperature. The total and Casimir entropies for the neutrino and electromagnetic fields at low temperature are also calculated and shown to be in agreement with the Nernst heat theorem. In addition to the Thermal Casmir effect, we study the Casimir-Polder effect. For this case, the Casimir-Polder interaction potential is evaluated for a polarizable microparticle and a conducting wall in the geometry of a cosmic string perpendicular to the wall. The general case of the anisotropic polarizability tensor for the microparticle is considered. The corresponding force is a function of the wall-microparticle and cosmic string-microparticle distances. Depending on the orientation of the polarizability tensor principal axes the force can be either attractive or repulsive. The asymptotic behavior of the Casimir-Polder potential is investigated at large and small separations compared to the wavelength of the dominant atomic transitions. We show that the conical defect may be used to control the strength and the sign of the Casimir-Polder force.